"Bringing in the Americans?" Assessing EU and U.S. post-Kyoto policies & options towards a Copenhagen Protocol in 2009 - Christian Hald-Mortensen (Danish Institute for International Studies (DIIS), 2008)
Bringing in the Americans is the first task for the UN-COP-15 for the Danish government along with its EU partners. The key contents of the EU's climate leadership towards the climate conference are assessed, such as the -20% by 2020 reduction target, the effort sharing agreement and reforms of the European Trading Scheme. EU climate leadership is both based on strong public support and economic features such as a lower energy intensity of production than the U.S. The EU and Danish strategy converge in promoting the concept of a 'low-carbon economy', based on first-mover advantage exports in renewables technology, such as wind power. The contents of the 'Danish example' are assessed; decoupling economic growth and emissions within a 'lowcarbon economy'-storyline. U.S. and EU policies diverged under the Bush administration that favored voluntary domestic measures towards industries and unilateral technology-based partnerships. The factors influencing the next President's climate policy such as increased support in public opinion, bottom-up developments among states, cities and in the business community are assessed, and so are factors that constrain a national climate policy, such as a high domestic reliance on coal. The dominant policy alternatives in the U.S. debate are evaluated. Ideas such as a carbon tax, emissions trading, a techno-optimist 'Manhattan Project on Climate Change' and a 5-10x spending scenario in energy R&D are explored in terms of their political feasibility. The analysis indicates that a national cap-and-trade could emerge, but the legislative deliberations to establish such a policy could protract beyond COP-15. Transatlantic convergence in emissions trading is however very likely in the next Kyoto commitment period from 2012 to 2017. The paper evaluates the work of Kyoto critics in terms of political feasibility and related Post-Kyoto proposals to empirical policy developments among the annex-I countries. Scholars have argued that an international framework for R&D in clean energy are needed, as past R&D efforts in clean energy has reduced the costs of electricity from solar panels. The section then discusses current energy R&D trends in the U.S. and in the OECD. Lowering the cost of key technologies could help to speed up diffusion of non-fossil-fuel sources, and would be a new form of directional leadership in climate policy, to be undertaken by the Annex-I countries.
Keywords: 330; Klimaschutz; Umweltabkommen; Internationale Umweltpolitik; Energieforschung; EU-Staaten; OECD-Staaten; USA